Synthesis and Characterization of New Bis-Schiff Bases Linked to Various Imide Cycles - Yassen, Tabarek Mohammed; AL-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2023)
This research includes the synthesis of new bis-Schiff bases linked to different imide cycles. There were some steps involved in the synthesis of the novel Schiff bases with succinimide, phthalimide, tetrachlorophthalimide, and tetrabromophthalimide cycles. The first step involved the preparation of 4,4`-bis[(4-aminophenyl) methyl benzylidene]tolidine (1) via the condensation reaction of 3,3’-dimethyl-(1,1’-biphenyl)-4,4’-diamine with 4-amino acetophenone. In the second step, compound 1 reacted with various cyclic anhydrides, affording bis-amic acid Schiff bases 2-5. In the third step, the products 2-5 were dehydrated using the fusion method to produce the target bis-imidyl Schiff bases 6-9. This work also involved the synthesis of bis-imidyl Schiff base 10 directly by fusion of compound 1 with 1,8-naphthalic anhydride. The prepared compounds were characterized depending on their FT-IR, 1H NMR, and 13C NMR spectra. The newly synthesized target compounds are expected to be very active biologically since their molecules are essential components of two active groups (imine and imide).